A Decentralized Routing Control Scheme for Data Communication Networks. (9th April 2013) - Si, Xueming; Zhu, Xun-Lin; Du, Xin; Xie, Xiangpeng
Abstract : This paper studies the decentralized routing control of data communication networks. Taking the physical constraints on the data flow and the network-induced delays into consideration, the decentralized routing control problem is reformulated as a constrained control problem, and the restriction of initial message lengths is no longer needed. By defining a general Lyapunov functional and applying a reciprocally convex combination technique to deal with the network-induced delays, less conservative and less complex designing conditions are obtained in terms of linear matrix inequalities (LMIs). A simulation example is also given to illustrate the effectiveness of the proposed designing scheme.